Analisis Kinerja Keuangan Dengan Menggunakan Perhitungan Gross Profit Margin (GPM), Net Profit Margin (NPM) Dan Return On Equity (ROE) Pada Pt. Pakuwon Jati Tbk Periode 2018-2021 - Binti Umaya; Indah Listyani; Edi Murdiyanto (STIKes Ibnu Sina Ajibarang, 2023)
A company needs to pay attention to financial performance in order to see how far the company's position by analyzing financial statements. This study aims to determine the financial performance of PT. Pakuwon Jati Tbk in 2018-2021 using the ratio of Gross profit Margin, Net Profit Margin and Return on assets. This type of research is descriptive with quantitative data taken secondarily from the balance sheet and income statement of PT. Pakuwon Jati Tbk for 2018-2021. Samples were taken from the population according to the saturated sampling method. The results of research that has been done show that the financial performance of GPM and NPM are in a good state that is above the industry average standard, GPM shows a decline while NPM shows unstable fluctuations. The results of financial performance with ROE in poor condition because it is below the industry average standard with fluctuations that are also unstable.